Building Family–Professional Partnerships with Culturally, Linguistically, and Economically Diverse Families of Young Children. (2nd October 2019) - Pearson, Jamie N.; Akamoglu, Yusuf; Chung, Moon; Meadan, Hedda
Abstract : Tamara is a single mother of two children, Isaiah (2 years old) and RaShawn (5 years old). She recently noticed that Isaiah was not developing in the same ways his older brother did when he was Isaiah's age. Unsure of where to go with her concerns about Isaiah's development, Tamara contacted a local University child development center that referred her to a developmental pediatrician. Following an initial visit and follow-up assessments, Isaiah was diagnosed with autism spectrum disorder (ASD), and the center gave her a referral for early intervention services. Although Tamara had heard of early intervention before, she was not sure how this service would help Isaiah and their family. She was especially concerned about practitioners coming into her home. 'What if I have to work?' She wondered. 'I don't even know these people, ' she thought. 'How can I help Isaiah?' she worried. Although Tamara had many reservations, she was also hopeful that her family's journey through early intervention would be a positive one.